Raman evidence for the successful synthesis of diamane. (November 2020) - Piazza, Fabrice; Kelvin Cruz; Monthioux, Marc; Puech, Pascal; Gerber, Iann
Abstract: Diamane was prepared from the exposure of bi-layer graphene to H radicals produced by the hot-filament process. A sharp sp 3 -bonded carbon stretching mode was observed by UV Raman spectroscopy while no sp 2 -bonded carbon peak was simultaneously detected. This is the first time that Raman spectra of genuine diamane are reported, which, meanwhile, are the very first evidence for the successful synthesis of genuine diamane. First principle calculations support possible full hydrogenation and confirm the hydrogenated AB configuration to be the most stable one. We believe those results constitute a milestone in the path towards the synthesis of high-quality diamane and open the door to large-scale production.